Co-creation of a sustainable image on social media : the case of five food brands - Smallegange, Cornelia (2017)
The food industry causes large environmental impacts globally. Different actors such as governments, brands and consumers however, are actively working on creating a sustainable society. In this study I investigate how brands and consumers co-create a sustainable image and which sustainable images they create. A multiple case study is conducted under five Dutch sustainable food brands by using content analysis of sustainability hashtags in firm- and user-generated posts generated between April 2016 and March 2017 on the social media platform Instagram. The hashtags where counted and categorized in ten sustainability categories which were defined in a test-phase using open coding principles. Major findings include that the sustainability images created by brands and their consumers can differ strongly. Both brands and consumers create most frequently sustainability hashtags related to healthy eating, lifestyle and dieting and less frequently hashtags related to environmental issues. The results do not show that brands strongly influence the user-generated sustainability hashtags with the sustainability hashtags they produce themselves on Instagram. Next to bringing newness value to the current sustainability research available, the study also offers practical implications. Namely that brands have only limited control of the sustainability image generated by their consumers on Instagram and that sustainability topics related to healthy eating, lifestyle and dieting seem to be important for the brand’s consumers active on Instagram.